Establishment of and egg and larval development index for lake sturgeon Acipenser fulvenscens - Eckes, Orey T. (My University, 2013)
With the development of production scale cultural practices many federal, state and tribal agencies have developed restoration plans consisting of managing and enhancing wild populations of lake sturgeon Acipenser fulvescens. A lake sturgeon egg and larval development index was created to incrementally chart development over time.This index provides a tool for accurately predicting and manipulating timing of development stages. Fish culturists and fisheries resources managers may use this index in ongoing restoration programs to assist in the recovery and restoration of lake sturgeon populations.
Keywords: Fishes -- Reproduction.; Fish stock assessment.; Fishes -- Development.